2023
DOI: 10.1111/1756-185x.14927
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with fertility intention among women with systemic lupus erythematosus in China: A cross‐sectional study

Qian Liang,
Xingxin Wang,
Qian He
et al.

Abstract: ObjectiveThis study aims to explore the status and influencing factors of fertility intention in women of childbearing age with systemic lupus erythematosus (SLE).MethodsA total of 158 SLE patients admitted to the Affiliated Hospital of Nantong University from February 2021 to February 2022 were selected for a cross‐sectional study. The dependent variable in this study was the fertility intention of lupus women of childbearing age, so the questionnaire was selected: “In view of your disease, do you plan to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The orbidity rate is higher in women, and men were more likely than women to experience end-organ damage and die. 2,3 Among all the influencing factors, the relationship between obesity and SLE has been widely studied, but it has not been fully clarified. A cross-sectional study showed that smoking is independently related to SLE, but body mass index (BMI) score is not related to SLE risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The orbidity rate is higher in women, and men were more likely than women to experience end-organ damage and die. 2,3 Among all the influencing factors, the relationship between obesity and SLE has been widely studied, but it has not been fully clarified. A cross-sectional study showed that smoking is independently related to SLE, but body mass index (BMI) score is not related to SLE risk.…”
Section: Introductionmentioning
confidence: 99%
“…Gender was related to SLE risk as well. The orbidity rate is higher in women, and men were more likely than women to experience end‐organ damage and die 2,3 . Among all the influencing factors, the relationship between obesity and SLE has been widely studied, but it has not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%